Ischemic stroke in a pediatric patient – a case report - Głaz, Aneta; Knop, Kinga; Kochanowska, Anna; Nowicki-Sak, Karol; Woźniak, Magdalena (Journal of Education, Health and Sport, 2022)
Background Childhood ischemic stroke (AIS) is a relatively rare disease with an estimated incidence of 1.3-13/100,000/year. It most commonly affects children under the age of 5. Major risk factors include arteriopathies, heart disease, hypercoagulable states and infections. Case report A 2-year-old patient was admitted to the Department of Neurology at the University Children’s Hospital in Lublin after suffering a head injury 3 days earlier. Neurological examination revealed features of left hemiparesis. A CT scan revealed an uncharacteristic hypodense, poorly demarcated area, an indication for further diagnostics. MR imaging revealed diffuse ischemic lesions. Angio-MR showed a lack of signal within the branches of the right posterior cerebral artery. Based on the clinical picture and additional examinations, a diagnosis of ischemic stroke was made and pharmacological treatment was implemented. To determine the cause of the stroke, an echocardiogram was performed, which showed flaccid atrial septal tissue with a defect and a trace left-right leak. Genetic testing for congenital thrombophilia confirmed a 4G/4G polymorphism in the PAI-1 gene. Conclusions Ischemic stroke is a life-threatening condition that requires prompt diagnosis and appropriate treatment. The relatively rare occurrence among children and nonspecific symptoms may result in difficulties in making a definitive diagnosis. Each case of stroke in children requires a comprehensive diagnosis including neuroimaging studies and identification of specific risk factors.